PENYULUHAN DAN APLIKASI SENAM NIFAS - Novita Wulandari; Nor Indah Handayani (STIKES NGUDIA HUSADA MADURA, 2020)
The puerperium (puerperium) is a period starting from the birth placenta and ending when the uterus organs return to their original state (before pregnancy), the length of the postpartum period is 6-8 weeks (Rahmawati, 2013). The method used by this community service will be implemented in Mlajah Bangkalan Village, followed by all postpartum mothers, residents of Mlajah village. With the following series of activities: postpartum mothers will be given leaflets about postpartum exercise and then given postpartum exercise material through extension activities, with the aim of increasing maternal knowledge about postpartum exercise so that it becomes a village that is free from the incidence of maternal mortality. This counseling will be held for approximately 30 minutes with a 10-minute material delivery session and a 20-minute discussion session. This activity will be preceded by a request for permission from the RT and RW of Mlajah village, after getting the permission we started preparing the materials. Postpartum exercise training which will be continued by midwives and cadres in Mlajah Bangkalan Village. Participants in all community activities (postpartum mothers) in Mlajah Bangkalan Village. During the postpartum counseling process, which consisted of establishing posyandu, postpartum exercise training and the entire program ran smoothly. All preparations have been made by the team and village midwives involved. The drawbacks that may occur in the implementation of postpartum gymnastics counseling are in the form of counseling activities with the daily activities of some cadres and mothers who work as farmers to coincide with harvest time. There are several programs that must be rescheduled.